DIGITAL LEADERSHIP TRANSFORMATION AND INNOVATIVE BEHAVIOR IN IMPROVING INTRAPRENEURSHIP INTENTION AND JOB PERFORMANCE IN ISLAMIC FINANCIAL INSTITUTION - Nasywa Aulia Zahra; Fatmah Bagis; Akhmad Darmawan; Dian Widyaningtyas (JURNAL ILMIAH EDUNOMIKA, 2026)
The development of digital leadership has becoming increasingly important as organizations face growing demands to adapt to technology-based work systems. This study aims to analyse the effect of digital leadership on intrapreneurship intention and job performance, as well as to examine the mediating role of innovative behaviour among employees of Islamic microfinance institutios BMTs. A quantitative approach was employed using the PLS-SEM method, involving 190 respondents selected through purposive sampling. The research instrument comprised four main constructs, namely digital leadership, innovative behaviour, intrapreneurship intention, and job performance. The results indicate that digital leadership has a positive and significant effect on innovative behaviour, intrapreneurship intention, and job performance. In addition, innovative behaviour is found to significantly enhance intrapreneurship intention and job performance. Another important finding reveals that innovative behaviour mediates the relationship between digital leadership and both outcome variables, indicating that innovative behaviour serves as a key mechanism through wich digital leadership is translated into employee performance and intrapreneurial outcome. Theoretically, this study strengthens the Resource-Based View by positioning digital leadership and innovative behavior as strategic intangible resources that contribute to sustainable competitive advantage in the context of digital transformation, particularly within Islamic microfinance institution. Practically, the findings suggest that BMTs should not only emphazise technological adoption but also focus on strengthening leaders’ digital competencies, fostering an innovation-oriented work culture, and providing structural support that enables employees to experiment and develop intrapreneurial initiatives aligned with organizational values and sharia principles.